Transformations in biblical literary traditions : incarnation, narrative, and ethics : essays in honor of David Lyle Jeffrey - Jeffrey, David Lyle, 1941-; Williams, Daniel H.; Donnelly, Phillip J. (Notre Dame : University of Notre Dame Press, 2014)
These essays not only acknowledge and clarify Jeffrey's achievement but also extend it in their attention to literary, philosophical, and religious works of the West.
Chapter 11: Medieval Biblical Drama in Post-Apartheid South AfricaChapter 12: Interdisciplinary Studies of Literature and Religion in China; Chapter 13: Friend and Guide; Bibliography of David Lyle Jeffrey's Published Works; Contributors; Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Bible -- Religious aspects -- Christianity -- History; Bible; Jeffrey, David L. -- 1941-; Bibel; Jeffrey, David L. -- 1941-; Spirituality -- Christianity -- History; Ethics; Exegesis & Hermeneutics; Biblical Studies; RELIGION; History & Culture; RELIGION / Ethics; Spirituality -- Christianity; Rezeption; Englisch; Literatur; Rezeption; Kultur; Literatur; Festschriften; History; Festschriften